An Examination of the Composition and Microstructure of Coarse Intermetallic Particles in AA2099-T8, Including Li Detection. (18th June 2018) - MacRae, Colin M.; Hughes, Anthony E.; Laird, James S.; Glenn, A. M.; Wilson, Nicholas C.; Torpy, Aaron; Gibson, Mark A.; Zhou, Xiaorong; Birbilis, Nick; Thompson, George E.
Abstract: Electron and proton microprobes, along with electron backscatter diffraction (EBSD) analysis were used to study the microstructure of the contemporary Al–Cu–Li alloy AA2099-T8. In electron probe microanalysis, wavelength and energy dispersive X-ray spectrometry were used in parallel with soft X-ray emission spectroscopy (SXES) to characterize the microstructure of AA2099-T8. The electron microprobe was able to identify five unique compositions for constituent intermetallic (IM) particles containing combinations of Al, Cu, Fe, Mn, and Zn. A sixth IM type was found to be rich in Ti and B (suggesting TiB2 ), and a seventh IM type contained Si. EBSD patterns for the five constituent IM particles containing Al, Cu, Fe, Mn, and Zn indicated that they were isomorphous with four phases in the 2xxx series aluminium alloys including Al6 (Fe, Mn), Al13 (Fe, Mn)4 (two slightly different compositions), Al37 Cu2 Fe12 and Al7 Cu2 Fe. SXES revealed that Li was present in some constituent IM particles. Al SXES mapping revealed an Al-enriched (i.e., Cu, Li-depleted) zone in the grain boundary network. From the EBSD analysis, the kernel average misorientation map showed higher levels of localized misorientation in this region, suggesting greater deformation or stored energy. Proton-induced X-ray emission revealed banding of the TiB2 IM particles and Cu inter-band enrichment.